Cataract Surgery in One-Eyed Patients: A Cohort Study of 100 Patients. (21st September 2021) - Charles, Alexis; Staccini, Pascal; Martel, Arnaud; Baillif, Stéphanie
Abstract : Purpose . To determine the course and outcomes of cataract surgery in one-eyed patients. Methods . This retrospective cohort study was conducted at the University Hospital of Nice, France. All one-eyed patients who underwent cataract surgery in their functional eye between January 2014 and December 2018 were included. A one-eyed patient was defined as having a visual acuity (VA) ≤20/200 in the other eye. Data were collected from the medical records and included the sociodemographic factors, the past medical history, data from the preoperative and postoperative clinical examinations, the surgical course, and the visual outcomes. Results . One hundred one-eyed patients with a mean age of 74.01 years were included (48 men/52 women). The mean preoperative VA was 20/100 (+0.74 logMAR). The VA ranged between 20/200 and 20/40 in 75 (75%) patients, was >20/40 in 8 (8%), and was <20/200 in 17 (17%) patients. Fifty-eight (58%) patients were operated on an outpatient basis. General or locoregional anesthesia was used in 29 (29%) and 9 (9%) patients, respectively. All cataract surgery procedures were performed by phacoemulsification. Five (5%) patients experienced intraoperative complications. Seventy-three (73%) one-eyed patients achieved a final VA ≥20/40. The mean final VA was 20/50 (+0.37 logMAR) (p < 0.001 ). Conclusion . A low rate of intraoperative complications was observed in one-eyed patients during cataract surgery. In most cases, a good visual recovery was achieved after cataract surgery, even in patients who experienced a surgical complication.